2016
DOI: 10.1371/journal.pbio.2000234
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Grey Zone of Speciation along a Continuum of Genomic Divergence

Abstract: Speciation results from the progressive accumulation of mutations that decrease the probability of mating between parental populations or reduce the fitness of hybrids—the so-called species barriers. The speciation genomic literature, however, is mainly a collection of case studies, each with its own approach and specificities, such that a global view of the gradual process of evolution from one to two species is currently lacking. Of primary importance is the prevalence of gene flow between diverging entities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
535
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(583 citation statements)
references
References 74 publications
40
535
4
4
Order By: Relevance
“…About 21% of the species (out of 47 where it was possible to give an assessment) appear not to be clearly identifiable based on nuclear data, but morphological separation of most of these ten or so species is also problematic (P. glauca and P. wesmaeli, ruficornis subgroup, armata subgroup, P. staudingeri and P. luteipes). Roux et al (2016) found in a recent study based on genome-scale data for 61 animal species/population pairs, that an intermediate "grey zone" of speciation exists. This zone, where taxonomy is often controversial, spanned from 0.5% to 2% of net synonymous divergence.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…About 21% of the species (out of 47 where it was possible to give an assessment) appear not to be clearly identifiable based on nuclear data, but morphological separation of most of these ten or so species is also problematic (P. glauca and P. wesmaeli, ruficornis subgroup, armata subgroup, P. staudingeri and P. luteipes). Roux et al (2016) found in a recent study based on genome-scale data for 61 animal species/population pairs, that an intermediate "grey zone" of speciation exists. This zone, where taxonomy is often controversial, spanned from 0.5% to 2% of net synonymous divergence.…”
Section: Discussionmentioning
confidence: 94%
“…excluding within population diversity). Among the 61 species/population pairs that Roux et al (2016) studied, gene flow between populations was always found to be prevalent when net synonymous divergence was below 0.5% and always absent when net synonymous divergence exceeded 2%. In the intermediate zone (net synonymous divergence 0.5%-2.0%), all degrees of reproductive isolation, from complete to none at all, were found (Roux et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These species fall at the high end of the continuum of divergence during which introgression persists among incipient species (Roux et al. 2016). We used experimentally bred F2 and BC1, with selection imposed implicitly, by the method of fertilization, and by our genotyping only individuals who survived to reproductive age (Bierne et al.…”
Section: Models and Resultsmentioning
confidence: 99%
“…
Genome-wide data obtained from even a small number of individuals can provide unprecedented levels of detail about the evolutionary history of populations and species [1], determinants of genetic diversity [2], species boundaries and the process of speciation itself [3]. Loire and Galtier [4] present a clear example, using the emblematic Galápagos giant tortoise (Chelonoidis nigra), of how multi-species comparative population genomic approaches can provide valuable insights about population structure and species delimitation even when sample sizes are limited but the number of loci is large and distributed across the genome.
…”
mentioning
confidence: 99%